A regulação descentralizada da governança corporativa: uma análise da criação dos segmentos de listagem do mercado organizado de valores mobiliários administrado pela Bovespa - Ribeiro, Victor Bourroul Holloway Ribeiro (2015)
The goal of this research is to analyze in a decentered regulation perspective the creation of Brazilian premium Corporate Governance segments. The goal of analyzing the creation of Brazilian premium Corporate Governance segments includes the description of the phenomenon by recognizing factors that led companies to change their behavior and the prescription of a normative argument formulated from the recognition of those factors. In the Corporate Governance literature, regulation is usually defined as a state-centered conception. Researches about premium Corporate Governance segments (Novo Mercado, Level 1 and Level 2) created by São Paulo Stock Exchange – Bovespa often adopt the state-centered definition of regulation. As opposed to a mandatory state regulation, these premium segments were classified as a private and self-regulatory phenomenon, conducted by the market. This analysis was followed by a normative argument that prescripts contractual or self-regulatory arrangements for policy makers with intention to promote specific Corporate Governance rules. However, the assumption of a state-centered regulation was contested by a decentered perspective. The decentered perspective argued that not only states are increasingly involved in complex collaborations and delegations with non-state actors to exercise regulation, but also non-states actors are regulating, setting standards, gathering information and enforcing rules. To handle those complex regulatory events, Julia Black formulated the concept of decentralized regulation, which was grounded on systems theory and the governance literature. Regulation in a decentering perspective is implemented by a network of interdependent state and non-state actors. Embracing Julia Black’s concept of decentralized regulation, the present research describes the creation of Brazilian premium Corporate Governance segments and formulates a normative argument deriving from the decentered perspective. Based on the results, the research concludes that the creation of Brazilian premium Corporate Governance segments did not involve just the parties of the Participation Agreement. Instead, it involved many interdependent state and non-state actors, which shared many mechanisms for the application of the regulation. Therefore, it is not possible to indicate the self-regulation and private legal instruments as the only factors that led companies and shareholders to alter their behavior and to adopt specific Corporate Governance rules. Accordingly, the normative argument that follows this analysis, rather than the prescription of self-regulation, is the prescription of the mobilization of the regulatory power fragmented among many state and non-state actors.